2009
DOI: 10.1007/s12098-009-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

Deletional mutations of dystrophin gene and carrier detection in eastern India

Abstract: About half the mothers of affected probands were not carriers of the deletion, underscoring the need to use real time techniques for carrier detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In relation to the PCR method, the MLPA method revealed 3 larger deletions, 4 deletions outside of the "hot spots" in the gene and 4 duplications in the probands, which confirms the effectiveness of the MLPA method in the detection of deletions/duplications in the dystrophin gene [11,[20][21][22]. The largest number of mutations was localized in the distal part of the gene (exons 45-55) in 61.3% (19/31) of cases, which is the most common localisation of deletions/duplications in sporadic DMD/BMD cases [23].…”
Section: Discussionsupporting
confidence: 63%
“…In relation to the PCR method, the MLPA method revealed 3 larger deletions, 4 deletions outside of the "hot spots" in the gene and 4 duplications in the probands, which confirms the effectiveness of the MLPA method in the detection of deletions/duplications in the dystrophin gene [11,[20][21][22]. The largest number of mutations was localized in the distal part of the gene (exons 45-55) in 61.3% (19/31) of cases, which is the most common localisation of deletions/duplications in sporadic DMD/BMD cases [23].…”
Section: Discussionsupporting
confidence: 63%
“…However, we could not validate the SEdel/dup by sequencing which may have revealed potential polymorphism or point mutation in the probe binding site. In a study conducted in the East Indian region, although the deletion rate of 65.7% was reported, deletion in the distal hot spot exonic region was noted in 82.61% of cases and that in the proximal hotspot, region was 10.87% [29]. In a South Indian MLPA based study, Vengalil et al reported deletions and duplications in 91% and 9% cases, respectively from a cohort of 279 DMD subjects [30] and reported exon 50 deletion to be the most common mutation.…”
Section: Discussionmentioning
confidence: 90%
“…Reported deletion detection rates vary widely, ranging between 31% and 73.86%. 11 24 These differences may be caused by many factors such as race, sample size and inclusion criteria. It has been suggested that the relatively low deletion detection rate in some studies is caused by the inclusion of other similar muscle diseases, because diagnosis was based mainly on clinical symptoms and did not require muscle biopsy.…”
Section: Discussionmentioning
confidence: 99%